Control strategy for high speed flywheel energy storage system based on voltage threshold of DC1500 V transit transportation traction grid. (November 2022) - Wang, Baonan; Yu, Xiaowan; Yang, Xiaoting; Zhang, Dan
Abstract: Energy storage equipment can play a unique advantage to recycle the regenerative braking energy of metro, of which flywheel energy storage system (FESS) has a good application prospect. At present, the control topology of FESS is two-level converter, and the DC voltage of FESS is mostly DC 750 V. High speed maglev-flywheel energy storage system (HSM-FESS) is used to recycle the braking energy in transit transportation. In order to achieve stable operation of the HSM-FESS, the control strategy based on the voltage threshold of the DC1500 V traction grid is adopted. At the same time, the Neutral Point Clamped (NPC) three-level control method of high speed maglev-permanent magnet motor (HSM-PMM) based on square wave modulation-two phase conduction (SWM-TPC) is proposed. A starting and braking simulation model of metro with HSM-FESS is built in MATLAB/Simulink, and the relevant simulation verification is completed.